2005
DOI: 10.1016/j.cell.2005.07.029
|View full text |Cite
|
Sign up to set email alerts
|

moody Encodes Two GPCRs that Regulate Cocaine Behaviors and Blood-Brain Barrier Permeability in Drosophila

Abstract: We identified moody in a genetic screen for Drosophila mutants with altered cocaine sensitivity. Hypomorphic mutations in moody cause an increased sensitivity to cocaine and nicotine exposure. In contrast, sensitivity to the acute intoxicating effects of ethanol is reduced. The moody locus encodes two novel GPCRs, Moody-alpha and Moody-beta. While identical in their membrane-spanning domains, the two Moody proteins differ in their long carboxy-terminal domains, which are generated by use of alternative reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
294
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(306 citation statements)
references
References 43 publications
10
294
0
2
Order By: Relevance
“…experiences action potentials, and Na ϩ channel inhibitors such as TTX are protective (Stys et al, 1992;Bechtold et al, 2005). In contrast, TTX does not inhibit Wallerian degeneration after acute injury (George et al, 1995;Press and Milbrandt, 2008; and this study), and action potentials do not appear to take place.…”
Section: Camentioning
confidence: 87%
“…experiences action potentials, and Na ϩ channel inhibitors such as TTX are protective (Stys et al, 1992;Bechtold et al, 2005). In contrast, TTX does not inhibit Wallerian degeneration after acute injury (George et al, 1995;Press and Milbrandt, 2008; and this study), and action potentials do not appear to take place.…”
Section: Camentioning
confidence: 87%
“…Invertebrate axons are insulated from their salt-rich environment through a glial-dependent BBB, which plays a crucial role in electrical and chemical insulation (Auld et al, 1995;Baumgartner et al, 1996;Bainton et al, 2005;Schwabe et al, 2005). Ultrastructural studies have demonstrated SJs between perineurial glial cells and inner glial cell membrane to form the structural basis of BBB of some insects (Carlson et al, 2000).…”
Section: Sjs As Molecular Barriers: a Common Theme In Axonal Insulationmentioning
confidence: 99%
“…Surface glia, the outermost layer of protection surrounding the larval and adult CNS, comprises two subtypes, the perineurial and subperineurial glia (SPG). These glial cells exclusively function as a blood-brain-barrier to prevent unwanted molecules over a certain size from entering the CNS [2,5,16] .…”
Section: Drosophila Gliamentioning
confidence: 99%
“…Surface glia, the outermost layer of protection surrounding the larval and adult CNS, comprises two subtypes, the perineurial and subperineurial glia (SPG). These glial cells exclusively function as a blood-brain-barrier to prevent unwanted molecules over a certain size from entering the CNS [2,5,16] .The protection is mainly mediated by SPG, which form [3,18] . In regards to size, SPGs have large and flatted cell bodies and are few in number, whereas perineurial glia have smaller cell bodies and higher numbers (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation